Fiscal Adjustment and Macroeconomic Re-balancing in Ireland - McCarthy, Colm (Statistical and Social Inquiry Society of Ireland, 2010)
In the five quarters from 2008 Q1 to 2009 Q2, Ireland.s real GNP, seasonally adjusted, has fallen by 13.5%. The unemployment rate has risen by eight points, labour force participation has fallen and emigration has resumed. The economic decline in Ireland exceeds by a large margin those being experienced by most other European countries, and constitutes the worst recession in Ireland since the early years of the Second World War. The policy challenge involves much more than fiscal consolidation, or recovery from a routine cyclical downturn.
Part of Symposium: Resolving Ireland's Fiscal Crisis (read before the Society, 26th November 2009)
Keywords: 314.15